Studi Dinamika Molekular Gas Karbon Dioksida dalam struktur es XVII - Yudha Arman; Artedi; Hasanuddin (Jurnal Penelitian Pendidikan IPA, 2025)
We conducted a molecular dynamics study on CO2 hydrate within the ice XVII structure to examine the molecular diffusion of CO2 molecules, as it is essential to the hydrate potential as a carbon capture. The simulated CO2 hydrate system used 324 water molecules and 90 CO2 molecules. We used the TIP4P/Ice model for water molecules, and the CO2 molecules were treated as united atom. The simulations were carried out at 273,15 K under various pressures of 200 MPa, 500 MPa, and 1000 MPa for 1,50 ns, with a step size of 1 fs. The results showed that the CO2 molecules were confined and freely moved inside the cage-like chiral tube along the c-axis of the ice XVII structure. No significant inter-cage hopping was observed during the evolution of all simulated systems. The diffusion coefficient values for CO2 molecules within the ice XVII structure were 5.03 × 10-8 cm2s-1, 2.45 × 10-8 cm2s-1, and 8.86 × 10-8 cm2s-1  for the respective pressure variations of 200 MPa, 500 MPa, and 1000 MPa, resulting in an inverse proportional with the system's pressure. A higher diffusion coefficient facilitates a faster the mass transfer and adsorption rate of CO2 in formation build up of the CO2 hydrate system.